FACTORS ASSOCIATED WITH FEMALE INFERTILITY - dos Santos Lima, Nathalia; Melise Pereira de Sousa, Maria; Eduarda Almeida de Souza, Cicera; Rolim de Oliveira, Rafaela; Caroline de Souza, Anne; Barros de Quental, Ocilma; de Lira Silva, Macerlane (Health and Society, 2023)
Female infertility is defined as the difficulty in getting pregnant after 12 months of regular sexual activity and no contraceptive use, according to the Society for Reproductive Medicine. Infertility can be a symptom or a warning of some health problem that can be associated with sterility. In recent times, Brazil has been going through a process of demographic transition, due to the decline in fertility. Some factors may be directly related to the inability of pregnancy that make ovulation difficult. The present study is justified by the fact that female infertility is still a subject loaded with social and archaic stigmas. In addition, it is a topic that needs to be addressed with some need, since intervention strategies need to be developed to normalize female infertility, covering the psychological, social, moral and ethical dimensions, since the woman shares the weight of the infertility differently with men. Thus, to carry out this research, a descriptive and exploratory study of the integrative literature review type was used, whose purpose will be to bring together different studies already published on the subject, in an objective, complete and impartial way on the subject. The searches were carried out from a bibliographic survey in scientific databases: LILACS, SCIELO and MEDLINE. Thus, from the selection of studies selected for the sample, the main outcomes on the topic in question were highlighted. In this context, the literature addresses some hypotheses that may be directly linked to female infertility. Based on this, evidence highlights endometriosis as the main predisposing factor for this circumstance. Endometriosis, even with all the clinical updates, is still considered an etiology.